EKSPLORASI KEARIFAN LOKAL DALAM PRAKTIK USAHATANI PADI RAWA LEBAK DI DESA PEMATANG BANGSAL - Mulyana, Eka (Institute of Computer Science (IOCS), 2025)
Lowland swamp rice farming reflects a traditional adaptation to wetland ecosystems that experience seasonal flooding and limited access to modern agricultural technology. In many such areas, including Pematang Bangsal Village in Banyuasin Regency, South Sumatra Province, these practices are increasingly under pressure from environmental change and the erosion of indigenous knowledge systems. The urgency of this research lies in the need to document and understand how local wisdom sustains agricultural productivity and community resilience in such fragile environments. This study aims to describe and analyze the forms of local wisdom embedded in lowland swamp rice farming in Pematang Bangsal, as well as to uncover the sociocultural values they embody. Using a qualitative case study design with a descriptive approach, the research involved 30 purposively selected farmers. Data collection methods included in-depth interviews, participatory observation, and document analysis, followed by thematic analysis. The findings reveal locally developed strategies such as floating seedbeds (ngambo), traditional transplanting methods (galeh), and collective harvesting practices (same-same). These techniques enhance both agricultural effectiveness and social solidarity. The study concludes that local wisdom plays a vital role in sustaining adaptive swamp-based agriculture and should be integrated into future policy and development planning.